2011
DOI: 10.2478/v10182-011-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Can Changes in Starch Content and Peroxidase Activity Be Used as Rooting Phase Markers for Rhododendron Leaf Bud Cuttings?

Abstract: We examined whether peroxidase activity in cutting bases and leaves and starch content in cutting bases can be used as rooting phase markers in the elepidote rhododendron cv. 'Babites Baltais' (Rhododendron L.). Changes in peroxidase activity in cutting leaves and bases, as well as starch content in cutting bases, were determined in relation to anatomical stages of rhizogenesis in leaf bud cuttings treated with 1% indole-3-butyric acid (IBA+) or without IBA (IBA-). The pattern of change of peroxidase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Different authors have observed variations in the starch content of cells during rhizogenesis (De Klerk et al 1999, Li and Leung 2000, Megre et al 2011. In alder, the starch content of the cells increased after the first 24 hours, and was most evident in the microcuttings treated with IBA.…”
Section: Discussionmentioning
confidence: 94%
“…Different authors have observed variations in the starch content of cells during rhizogenesis (De Klerk et al 1999, Li and Leung 2000, Megre et al 2011. In alder, the starch content of the cells increased after the first 24 hours, and was most evident in the microcuttings treated with IBA.…”
Section: Discussionmentioning
confidence: 94%
“…The content of soluble sugars on the 2nd day of root induction phase was positively correlated with rooting e ciency, and on the 7th with all studied rooting characteristics. Involvement of carbohydrates, particularly soluble sugars, in adventitious rooting process is usually related to their role as a carbon and energy source (Megre et al 2011, Otiende et al 2017. In this respect TSS can be considered the most impactful biomarker in studied species, and factors stimulating TSS synthesis could potentially enhance its rooting ability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, study of these phases allows understanding the role of different rooting promoting treatments on biochemical course of the adventitious root formation. Previously we showed a correlation between peroxidase activity in leaves and bases of rhododendron leaf-bud cuttings, which allows to perform simultaneous anatomical study and peroxidase activity assay on the same plant material (Megre et al 2011). Thus, in current study rhododendron leaves were used for peroxidase activity assay.…”
Section: Introductionmentioning
confidence: 90%
“…Many studies have been performed to understand anatomical, physiological and biochemical processes during adventitious root formation and it is considered that adventitious rooting anatomically and biochemically consists of three subsequent phases: induction, initiation and expression (Gaspar et al 1994;Husen 2008;Naija et al 2008). In several plant species, including rhododendrons, changes in peroxidase activity have been suggested as a biochemical marker for these phases (Metaxas et al 2004;Syros et al 2004, Naija et al 2008Megre et al 2011). Thus, study of these phases allows understanding the role of different rooting promoting treatments on biochemical course of the adventitious root formation.…”
Section: Introductionmentioning
confidence: 99%